Estudos de citotoxicidade e genotoxicidade de Eleutherine plicata Herb - GALUCIO, Natasha Costa da Rocha (Universidade Federal do Pará, 2017)
The purpose of this study was phytochemical studies of E. plicata, and to evaluate the cytotoxicity, the role of oxidative stress and genotoxicity. The powder of E. plicata bulbs underwent maceration with ethanol, the solution concentrated to residue in rotaevaporator. The ethanol extract was subjected to fractionation by open column chromatography over silica gel, being used as the mobile phase solvents of increasing polarity. The dichloromethane fraction was subjected to fractionation by preparative layer chromatography using dichloromethane as mobile phase, and 3 subfractions obtained. The ethanol extract, fractions and subfractions were subjected to chromatographic and spectrophotometric analysis. All samples were subjected to the tests: cellular viability (MTT), the antioxidant capacity (DPPH), comet and micronucleus assays. From the ethanol extract obtained a rich fraction naphthoquinone (dichloromethane fraction). Fractionation of this led to the isolation of: S1, S2 (major fraction), and fraction of minority S3 (unidentified, not tested). Chromatographic studies and spectrophotometric allowed the identification of S2 (isoeleuterin). Fractionation contributed positively to cytotoxicity on VERO cells, the sample being more cytotoxic to S1. The cytotoxicity in HepG2 cells was concentration dependent, being the fractionation did not contribute positively to this. Also, over time, the longer the exposure time, the lower the cytotoxicity to HepG2 cells. The maximum antioxidant activity was observed for subfraction S1, and this low genotoxicity possessed by both methods and it was the most cytotoxic. The dichloromethane fraction has an intermediate antioxidant capacity, but had a high genotoxicity in micronucleus assay. The isoeleuterin (S2) was lower antioxidant capacity, lower cytotoxicity and genotoxicity conflicting results. The ethanol extract possessed the lowest antioxidant capacity, moderate genotoxicity and lower cytotoxicity. When analyzing the results occur that: a subfraction S1 is the most promising candidate as the antimalarial drug, as have cytotoxicity and genotoxicity rates at acceptable levels. The isoeleuterin needs additional research on 11 genotoxicity. Regarding the dichloromethane fraction was not advisable to use for the development of an antimalarial drug, since it is more genotoxic.